2016
DOI: 10.1111/jocn.13099
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving to persons living with HIV/AIDS: experiences of Vietnamese family members

Abstract: Health care providers should consider gender, age and culture of family members of persons living with HIV/AIDS. Knowledge about HIV/AIDS, provision of care at home and in hospital, and support groups should be developed and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
2
18
0
2
Order By: Relevance
“…In Thailand, Lee, Li, Jiraphongsa, and Rotheram-Borus (2010) examined how depression negatively affected the levels of caregiver burden and social support positively impacted caregiver’s quality of life. A study in Vietnam reported similar findings as previous studies that family caregivers lack education and provision of care and mostly kept a secret about family member’s HIV status to avoid stigma (Lundberg, Doan, Dinh, Oach, & Le, 2016). …”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In Thailand, Lee, Li, Jiraphongsa, and Rotheram-Borus (2010) examined how depression negatively affected the levels of caregiver burden and social support positively impacted caregiver’s quality of life. A study in Vietnam reported similar findings as previous studies that family caregivers lack education and provision of care and mostly kept a secret about family member’s HIV status to avoid stigma (Lundberg, Doan, Dinh, Oach, & Le, 2016). …”
Section: Introductionsupporting
confidence: 81%
“…Nonetheless, spouses were rarely studied as caregivers of PLH. A Vietnamese study briefly examined gender and found no difference in regards to total caregiver burden; however, it documented several differences between older and younger caregivers in some categories of measured caregiver burden (Lundberg et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…17 Strengthening the link between clinics and families could be an important way to improve long-term retention in care and adherence. 29 While having trusted relationships with providers was an important facilitator of retention in care, stigma and discrimination related to HIV, sexual orientation, and/or gender identity created barriers to staying in care, as has been found in other settings. 10 There is a need for ongoing sensitization and capacity building with all staff and clinical care providers in order to continue improving the overall environment of the clinics for these key populations.…”
Section: Discussionmentioning
confidence: 99%
“…This internalization can apply to family members as well. In Vietnam, family caregivers described a perceived need to keep their loved one’s status a secret to avoid stigma and discrimination, causing great fear, anxiety, and frustration, and limiting social support (35). …”
Section: Introductionmentioning
confidence: 99%